Adaptive particle representation of fluorescence microscopy images - Bevan L. Cheeseman (Nature Portfolio, 2018)
Modern microscopes can generate high volumes of 3D images, driving difficulties in data handling and processing. Here, the authors present a content-adaptive image representation as an alternative to standard pixels that goes beyond data compression to overcome storage, memory, and processing bottlenecks.